Long-term optimization of Egypt's power sector: Policy implications - Md. Alam Hossain Mondal; Claudia Ringler; Perrihan Al-Riffai; Hagar Eldidi; Clemens Breisinger; Manfred Wiebelt (Energy, 2019)
This paper presents an evaluation of energy supply strategies for Egypt's power sector and identifies prospects to meet rising electricity demand while addressing energy security and low-carbon development issues. We apply the TIMES energy system model to examine Egypt's energy policy goals as reflected in Egypt's Vision 2030, and specifically: (a) targeted power generation based on renewable energy under two different scenarios; (b) targeted carbon dioxide (CO2) emissions' mitigation toward low-carbon society development; and (c) constraints on natural gas production for power generation. The quantitative results from the model suggest a need for diversification from predominantly natural gas to a mix of renewable and conventional energy sources in order to improve energy security, reduce dependency on fossil fuels, and reduce carbon dioxide emissions, with the level of diversification changing with different policy options. Although total energy system cost is projected to increase the effects on fossil-fuel dependency, diversity of energy supply-mix, marginal electricity generation price, and GHG mitigation indicate that it may be wise to target promotion of renewable energy for power generation and develop a low-carbon society.
Keywords: 330; Energy policy; Optimization; Climate change; Energy security; TIMES model